A study on effects of slug flow on dynamic response and fatigue damage of risers. (1st December 2020) - Jeong, Hyeonsu; Jang, Beom-Seon; Du Kim, Jeong; Park, Gunil; Choi, Jaewoong; Lee, Dongyeon
Abstract: A slug flow (a series of liquid slug separated by a gas pocket) is a flow pattern that often occurs in a multiphase oil and gas riser system. Dynamic and structural responses of a riser can be increased by time varying forces of the slug flow. In this paper, a methodology has been developed for the evaluation of the effects of slug flow on the dynamic and structural responses of different types of risers. A global dynamic analysis is carried out to calculate the dynamic responses of a riser induced by the slug flow and environmental loads. Idealized regular slug flow are considered as a time dependent variation of internal fluid flow according to results of multiphase flow simulations. Local stress and fatigue damage of risers are estimated using an in-house program, which considered the hysteresis effects of a flexible riser. The verifications of the numerical model and slug modeling method are carried out prior to the parametric study. Parametric studies are performed in order to quantitatively identify the design conditions that are most affected by the slug flow. The riser system connected to a moored vessel in deep-water is considered for the parametric study. Different riser materials, riser configurations, production stages (flow rates) and environmental conditions are considered. Study results demonstrate that the dynamic effects due to slug flow are significant for a flexible lazy wave riser, middle production stage and mild sea states. While the maximum value of dynamic loads is slightly changed even with considerable slug flow, range of fluctuation (standard deviation) of bending curvature is substantially increased under mild sea states with high probability of occurrence. This means that a main impact of the slug flow is the increased fatigue damage of a riser structure. The fatigue damage with and without slug flow has been estimated in order to investigate the fatigue contribution of the slug flow. Highlights: Effects of slug flow on dynamic response and fatigue damage of risers are estimated using a global dynamic analysis. Parametric studies are performed to quantitatively identify design conditions that are most affected by the slug flows. Characteristics of slug flows for various riser type and production stages are obtained from multiphase flow simulations. The effects of slug flow are most pronounced in a flexible lazy wave riser under mild sea states. Slug flow increases fatigue damage of riser structures due to greater variations of bending curvature.